A Late Glacial family at Trollesgave, Denmark. (February 2015) - Donahue, Randolph E.; Fischer, Anders
Abstract: Microwear analysis is applied to reconstruct the function and social organisation at the Late Glacial site of Trollesgave, Denmark. As with Bromme Culture sites in general, the lithic assemblage consists of primarily three types of tools. There is a strong association between these types and their use: end scrapers for dry hide scraping; burins for working hard material, primarily bone; and tanged points primarily for projectile tips. Nearly all divergence from this pattern can be referred to as the activities of children, the products and workshops of which have previously been identified. Based on the combined information from microwear analysis, flint knapping and spatial distribution of artefacts, the assemblage is inferred as the traces of a single family hunting (and fishing) occupation. Highlights: There is a strong association between tool types and tool use. There is one master knapper, two less proficient knappers, and a beginner knapper. The predominance of dry hide over fresh hide scraping indicates a woman was on site. There is just one structure and one hearth and three dissimilar activity areas. The site was occupied by a nuclear family: 2 adults (male and female) and 2 children.